2007
DOI: 10.1515/cclm.2007.122
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators and specifications for key processes in clinical laboratories: a preliminary experience

Abstract: The process indicators reflect the state-of-the-art of the laboratories comprising our working group. Current performance for the analytical phase is satisfactory because it is entirely in the hands of the laboratory, while the main problems in extra-analytical phases reside in activities performed outside the laboratory (sample collection and transport, as well as non-electronic report delivery).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 1 publication
1
9
0
1
Order By: Relevance
“…In the preliminary study on quality indicators, error rates in preanalytical indicators such as erroneous request, erroneous sample, and samples that were not taken were found as 4.1%, 5% and 1.7%, respectively ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary study on quality indicators, error rates in preanalytical indicators such as erroneous request, erroneous sample, and samples that were not taken were found as 4.1%, 5% and 1.7%, respectively ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Errors related to ID or barcode linkage can cause delay or incorrect ordering of analysis, thereby delivering inaccurate test results to the patient [2,20,22]. Still, despite the intervention, 16% of the IG PHC phlebotomists reported that they sometimes labelled the test tube at a later occasion or allowed somebody else to label afterward, which is unacceptable.…”
Section: Discussionmentioning
confidence: 99%
“…A common reason for specimen rejection and renewed sampling is specimen haemolysis, which most often is due to incorrect specimen collection including prolonged venous stasis and not sufficiently filled tubes [1,10,17-19]. Common specimen handling errors include incorrect test tube labelling [2,15,20,21], incorrect test request management, missing tubes, and transport errors [2,8,10,14,22]. …”
Section: Introductionmentioning
confidence: 99%
“…При этом сохраняется недостаток внимания к внелабораторным этапам исследования, что резко контрастирует с многочисленными исследованиями разнообразных ошибок, которые происходят на пре-и постаналитических этапах. В последнее время в некоторых странах и регионах (Австралия и Новая Зеландия [8], Бразилия [9], Каталония [10]) уже разработаны программы оценки ИК внелабораторных этапов исследования, в других подобные исследования анонсированы (Великобритания [11,12], Китай и Хорватия [13]).…”
unclassified